1988
DOI: 10.1016/0266-7681(88)90130-1
|View full text |Cite
|
Sign up to set email alerts
|

Occupation as a risk factor for impaired sensory conduction of the median nerve at the carpal tunnel

Abstract: 471 industrial employees from 27 occupations in four industries were surveyed to evaluate the role of occupational hand activity as a risk factor for slowing of sensory conduction of the median nerve at the carpal tunnel. After age-adjusting the latency values, slowing of the sensory fibres of the median nerve was found in 39% of the subjects and in 26% of the hands. No consistent association was found between the type and the level of occupational hand activity and the prevalence or the severity of slowing. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0
6

Year Published

1990
1990
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(64 citation statements)
references
References 13 publications
4
54
0
6
Order By: Relevance
“…In our survey of the literature, there were 21 articles and reports that met the established criteria: 15 crosssectional studies in which 32 occupational or exposure groups had been studied (table 1) (6,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) and six case-referent studies (table 2) (25)(26)(27)(28)(29)(30). All of these studies involved prevalent cases of CTS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our survey of the literature, there were 21 articles and reports that met the established criteria: 15 crosssectional studies in which 32 occupational or exposure groups had been studied (table 1) (6,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) and six case-referent studies (table 2) (25)(26)(27)(28)(29)(30). All of these studies involved prevalent cases of CTS.…”
Section: Resultsmentioning
confidence: 99%
“…Surgical release of the median nerve at the wrist was also accepted as CTS, since both symptoms and signs are a general requirement for carpal tunnel surgery (5). Furthermore we included a study of occupational groups in which only nerve conduction was measured (6).…”
Section: Methodsmentioning
confidence: 99%
“…Mean force requirements on the forearm flexor (N=45) muscles while deboning has been assessed by electromyography (14), which showed a static activity (P=0.1) of between 8% and 9%, a median activity (P=0.5) of between 25% and 30%, and a peak activity (P=0.90) of about 60% of a mean maximal hand grip of 54.6 kg. In an evaluation of force requirements (15) in worktasks designed to simulate combined highforce and high repetition exposure, the corresponding values were IS%, 19.1%, and 69.5%, respectively, for 6 subjects. Slaughterhouse workers performing deboning assist constantly and actively with the nondominant hand in tearing, lifting, turning, and holding the 6-12 kg body parts.…”
Section: Discussionmentioning
confidence: 99%
“…If the answers concerning hand exposures among the referents reflected the same level of hand exposure as among the slaughterhouse workers, then the risk of CTS in relation to hand intensive work would have been negatively biased. When underlying exposures are measured using job titles (7,(18)(19)(20), misclassification can occur from differences in the underlying exposure (force, repetitivity, level, duration of exposure, vibration) among persons with the same job title. Indirect exposure classification based on, for example, ergonomic observations (21,22) leaves the question open of which types of jobs are being categorized whether the measured exposures are of more relevance than the unmeasured ones.…”
Section: Discussionmentioning
confidence: 99%
“…Industrial workers with exposure to repetitive hand exertion were found to have significantly smaller sensory amplitudes (P Ͻ .05) and longer motor and sensory latencies (P Ͻ .001) in tests of nerve conduction. On the other hand, Nathan et al 17 failed to find an association between the specific type of occupational hand use and the prevalence or severity of impaired sensory conduction of the median nerve at the carpal tunnel in 471 industrial employees from 27 occupations. In a follow-up study 18 5 years later involving 67% of the original group of 471 employees, the same group of investigators reported that there continued to be no significant change in the prevalence of median nerve neuropathy.…”
Section: Epidemiological Studies Set the Stagementioning
confidence: 99%